Learning By Doing in New Firms and the Optimal Rate of Inflation - Henning Weber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Empirical data suggest that new fi rms tend to grow faster than incumbent firms in terms of their productivity. A sticky-price model with learning-by-doing in new firms fi ts this data and predicts that for plausible calibrations, the optimal long-run inflation rate is positive and between 0.5% and 1.5% per year. A positive long-run inflation rate helps the fast-growing new fi rms to align their real price with their idiosyncratic productivity growth. In contrast, the standard sticky-price model without learning-by-doing in new fi rms predicts an optimal long-run inflation rate near zero. In a two-sector model with learning-by-doing in new firms, the policy tradeo that arises between new and incumbent firms is considerably more severe than the policy tradeo that arises between economic sectors.
Keywords: E31; E52; E61; 330